The Relationship Between Mindfulness and Cognitive Flexibility of University Students - Tugce PEKER AKMAN (Muhammed Yıldız, 2021)
The aim of present study was to examine the associations among mindfulness and cognitive flexibility. The study group consisted of 244 university students, 187 female and 57 male. The age of the university students in the study group ranged from 18 to 34 with a mean age of 20.27. Mindful Attention Awareness Scale, Cognitive Flexibility Inventory and personal information form, which collect demographic information of the participants, were used in the data collection process. In order to investigate the relationships between mindfulness and cognitive flexibility (alternative and control), Pearson's product-moment correlation coefficients were determined. According to correlation analysis results, significant relationships between mindfulness and cognitive flexibility and alternatives and control, which are sub-factors of cognitive flexibility, were determined. Multivariate analysis of variance (MANOVA) was used to determine whether the relationship between mindfulness and cognitive flexibility made a significant difference according to gender. According to the Manova test results, it was determined that gender has a significant effect on the relationship between mindfulness and cognitive flexibility. Simple linear regression analysis was performed to determine to what extent mindfulness predicts cognitive flexibility. As a result of the regression analysis, it was concluded that mindfulness explains 29.4% of the total variance of cognitive flexibility. Based on the results of the research, psychoeducational programs can be prepared to develop mindfulness and cognitive flexibility in activities performed in the field of guidance and psychological counseling.